2013
DOI: 10.1176/appi.ajp.2013.12121599
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline, Smoking Cessation, and Neuropsychiatric Adverse Events

Abstract: Objective In 2009 FDA issued a black box warning for varenicline and neuropsychiatric events. We studied efficacy (smoking cessation) of varenicline, and safety (neuropsychiatric events) in both randomized clinical trials (RCTs) and a large observational study. The observational study was included to determine the generalizability of the RCT findings to the general population. Method RCTs: Re-analysis of all 17 placebo controlled RCTs (n=8027) of varenicline conducted by Pfizer using complete intent-to-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 15 publications
4
75
1
3
Order By: Relevance
“…The presence of adverse effects was noteworthy, as the P value was close to significant after regression analysis, and it may be a factor affecting the success of pharmacotherapy indirectly. The reported adverse effects of varenicline, the most frequently prescribed agent used in our subjects, include the increased risk for cardiovascular accident development, 34 nausea, [35][36][37][38] abnormal dreaming, sleeplessness, 36,38 headache, 37,38 depression, and possible serious psychiatric conditions. 39,40 The most frequent adverse effect we observed with varenicline was nausea.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of adverse effects was noteworthy, as the P value was close to significant after regression analysis, and it may be a factor affecting the success of pharmacotherapy indirectly. The reported adverse effects of varenicline, the most frequently prescribed agent used in our subjects, include the increased risk for cardiovascular accident development, 34 nausea, [35][36][37][38] abnormal dreaming, sleeplessness, 36,38 headache, 37,38 depression, and possible serious psychiatric conditions. 39,40 The most frequent adverse effect we observed with varenicline was nausea.…”
Section: Discussionmentioning
confidence: 94%
“…A review of the neuropsychiatric safety of varenicline, including data from 22 industry-and 17 non-industry-funded RCTs that involved 10 761 participants, found no increased risk of suicide or attempted suicide, suicidal ideation, depression, irritability, aggression or death in participants taking varenicline compared with those taking placebo, 20 which is consistent with other reviews. 21,22 An RCT mandated by the US Food and Drug Administration, which assessed the incidence of neuropsychiatric events among 8144 participants who smoke and were given treatment with varenicline, bupropion, nicotine replacement therapy patches or placebo, found no increased risk of neuropsychiatric events attributable to varenicline or bupropion relative to nicotine replacement therapy or placebo. 23 Data from surveillance studies involving patients using bupropion for smoking cessation showed an increased risk of seizures; 24,25 safety could be improved if clinicians avoid treatment with bupropion in patients at risk of seizures, including older adults.…”
Section: Medications For Smoking Reductionmentioning
confidence: 99%
“…24 In a meta-analysis where randomized controlled studies were re-evaluated, varenicline proved to be successful in both the notreatment group and the bupropion group. 25 According to the results of this research, participants remaining longer in their treatment regardless of the modality stay free of smoking for longer periods. In their research, Schnoll et al found that participants remaining for 24 weeks in their treatment proved to be more successful in quitting smoking compared to participants remaining for 8 weeks in their treatment.…”
Section: Discussionmentioning
confidence: 78%